Price, Brand Image, and Promotion's Impact on Parepare City Online Transportation Customers Loyalty - Annur, Destina Efri; Semaun, Syahriyah; Musmulyadi, Musmulyadi; Muliati, Muliati; Bahri, Andi (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this study is to examine the variables that affect the loyalty of Parepare City's online transportation users, namely those who use Grab, Maxim, and Gojek. The research methodology combines an associative approach with quantitative descriptive research of the field study type. With a sample size of 90 samples and certain criteria, the population consists of the Parepare City Community users of Grab, Maxim, or Gojek. A Google Form questionnaire was utilised to collect data for the study. The study's findings indicate: Price and customer loyalty have an impact on each other, according to the t-test results, which indicate a value of 0.000 < 0.05. With a score of 0.000 < 0.05, brand image has an impact on customer loyalty. Additionally, there is a 0.007 < 0.05 correlation between customer loyalty and promotion. Additionally, according to the f test results, which indicate that the computed f value is higher than the f table where 52.912 > 2.71, it can be concluded that pricing, brand image, and promotion all significantly affect consumer loyalty either separately or in combination.Keywords: Brand Image, Customer Loyalty, Price, Promotion